Flash - Miles, Ellen (New York : Scholastic, 2006)
While vacationing in the country, dog-lovers Charles and Lizzie Peterson help find a home for an abandoned border collie named Flash.
4.3
3-6
630L
N
Keywords: Dogs -- Fiction; Animals -- Infancy -- Fiction; Pets -- Fiction; Dogs -- Fiction; Animal babies -- Fiction; Pets -- Fiction; Dogs -- Fiction; Animals -- Infancy -- Fiction; Border collie -- Fiction; Dog adoption -- Fiction; Puppies -- Fiction